Liquid-liquid phase separation: a new perspective on respiratory diseases - Wang, Li; Wang, Yongjun; Ke, Zhangmin; Wang, Zexu; Guo, Yufang; Zhang, Yunlei; Zhang, Xiuwei; Guo, Zhongliang; Wan, Bing (Frontiers in Immunology, 2024)
Liquid-liquid phase separation (LLPS) is integral to various biological processes, facilitating signal transduction by creating a condensed, membrane-less environment that plays crucial roles in diverse physiological and pathological processes. Recent evidence has underscored the significance of LLPS in human health and disease. However, its implications in respiratory diseases remain poorly understood. This review explores current insights into the mechanisms and biological roles of LLPS, focusing particularly on its relevance to respiratory diseases, aiming to deepen our understanding and propose a new paradigm for studying phase separation in this context.